2012
DOI: 10.1007/s11033-012-2023-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in metabolizing genes NQO1, NQO2, MTHFR and risk of prostate cancer: a study from North India

Abstract: Quinone oxidoreductases (NAD(P)H): quinone oxidoreductase 1 (NQO1) and NRH: quinone oxidoreductase 2 (NQO2) are an antioxidant enzyme, important in the detoxification of environmental carcinogens. Methylene-tetra-hydrofolate reductase (MTHFR), plays a role in folate metabolism and may have oncogenic role through disruption of normal DNA methylation pattern, synthesis, and impaired DNA repair. In a case-control study, genotyping was done in 195 PCa and 250 age matched unrelated healthy controls of similar ethni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…hNQO2 has a common SNP (C659T or L47F) that does not affect enzymic activity but makes hNQO2 more susceptible to proteolysis (Megarity et al , ). hNQO2 SNPs have been linked to prostate cancer (Mandal et al , ), colorectal cancer (Chen et al , ) and prognosis in breast cancer (Hubackova et al , ). hNQO2 has been associated with the activation of chemotherapeutics (Celli et al , ; Jamieson et al , ), and hNQO2 SNPs are associated with the cardiotoxicity of the anthraquinone idarubicin (Megias et al , ).…”
Section: Nitrofuran and Other Nitroaromatic Drug Activation By Azoredmentioning
confidence: 99%
“…hNQO2 has a common SNP (C659T or L47F) that does not affect enzymic activity but makes hNQO2 more susceptible to proteolysis (Megarity et al , ). hNQO2 SNPs have been linked to prostate cancer (Mandal et al , ), colorectal cancer (Chen et al , ) and prognosis in breast cancer (Hubackova et al , ). hNQO2 has been associated with the activation of chemotherapeutics (Celli et al , ; Jamieson et al , ), and hNQO2 SNPs are associated with the cardiotoxicity of the anthraquinone idarubicin (Megias et al , ).…”
Section: Nitrofuran and Other Nitroaromatic Drug Activation By Azoredmentioning
confidence: 99%
“…Single nucleotide polymorphisms result in the expression of different protein variants of NQO1. The two most prevalent variants in the human population are NQO1*2 (NQO1 609C>T; NQO1 P187S; allelic frequency: 0.22-0.47) and NQO1*3 (NQO1 465C>T; NQO1 R139W; allelic frequency: 0.00-0.05), which are connected to a higher risk for specific cancers [5][6][7][8][9][10][11]. Several studies have focused on NQO1*2 and have shown a reduction or even a loss of the enzymatic activity of NQO1 P187S [12][13][14].…”
mentioning
confidence: 99%
“…Moreover, 2 studies were excluded because they did not provide the exact genotypes and the OR (95%CI) for the association between gene polymorphisms and prostate cancer risk could not be estimated (Zacho et al, 2011;Jackson et al, 2013). As a result, 21 case-control studies were included in our meta-analysis (Kimura et al, 2000;Heijmans et al, 2003;Cicek et al, 2004;Singal et al, 2004;Van Guelpen et al, 2006;Johansson et al, 2007;Reljic et al, 2007;Marchal et al, 2008;Stevens et al, 2008;Collin et al, 2009;Muslumanoglu et al, 2009;Cai et al, 2010;Safarinejad et al, 2010;Wu et al, 2010;Küçükhüseyin et al, 2011;Fard-Esfahani et al, 2012;Kobayashi et al, 2012;Mandal et al, 2012;de Vogel et al, 2013;López-Cortés et al, 2013;Ghasemi et al, 2014).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…This suggests that genetic factors may have different impacts on the risk of prostate cancer in different populations. Several recent studies (Fard-Esfahani et al, 2012;Kobayashi et al, 2012;Mandal et al, 2012;de Vogel et al, 2013;Jackson et al, 2013;López-Cortés et al, 2013;Ghasemi et al, 2014) investigated the association between MTHFR gene polymorphisms and prostate cancer risks, but found conflicting results. Thus, the impact of MTHFR gene polymorphisms (C677T and A1298C) on prostate cancer risk remains unclear.…”
Section: Introductionmentioning
confidence: 99%